The case fatality rate of COVID‐19 during the Delta and the Omicron epidemic phase: A meta‐analysis. Issue 2 (7th February 2023) - Kim, Kisong; Cho, Kyuyeon; Song, Junmin; Rahmati, Masoud; Koyanagi, Ai; Lee, Seung Won; Yon, Dong Keon; Il Shin, Jae; Smith, Lee
Abstract: As coronavirus variants are constantly occurring, we tried to understand more about the omicron and delta variants that have hit the world. We provided dynamic information on the case fatality rate (CFR) of the Omicron variant over time and to compare it with that of the Delta variant through meta‐analysis. Twenty‐four countries were selected by submission counts, submission dates, and confirmed cases. We defined the Delta or the Omicron epidemic period for individual countries as when each variant is over 90%. We further analyzed the Omicron period by dividing it into the initial plateau, increasing, and decreasing phases according to the number of newly confirmed daily cases. Finally, the meta‐analysis examined the summary and between‐study heterogeneity. The CFR of COVID‐19 during the Omicron epidemic was lower than that during the Delta epidemic (odds ratio [OR]: 0.252, 95% confidence interval [CI] 0.205−0.309). The CFR of COVID‐19 during the initial plateau phase of Omicron was higher than during other phases. (OR: 1.962, 95% CI 1.607−2.397). The CFR of COVID‐19 during the increasing phase was lower than during the decreasing phases (OR: 0.412, 95% CI 0.342–0.498). The Omicron variant had lower CFR compared to the Delta variant, and the initial plateau phase had higher CFR compared to the noninitial phases. These results can help establish global health policies for COVID‐19 in the future.